Ecomorphological Diversity in the Patagonian Assemblage of Bats from Argentina - Giménez, Analía Laura (2017)
Patagonian bats are represented by only insectivorous species, five vespertilionids and one molossid species. They constitute an interesting assemblage of temperate species that remains poorly studied. Here we uncover ecomorphological patterns of Patagonian bats using craniodental morphology, aerodynamic measurements, and external bodily characters. Multivariate analysis was applied to characterize morphometric variation of each dataset separately and in combination. We explored the segregation of species in morphospace, and the importance of phylogeny in the assemblage organization. We used a phylogenetic comparative method to evaluate historical effects on the morphofunctional structure. Our results indicated that the species of the Patagonian assemblage segregate in dimensions of morphospace by size and morphology, which would be related to prey selection (trophic differences) and habitat use (different styles of flight). We also demonstrated the impact of different cladogenetic events of the evolutionary history of species on the structuring of the Patagonian assemblage, with the successive addition of non-overlapping, well-defined morphofunctional types imported from other South American regions, and whit speciation events that resulted in species-level endemisms (Myotis chiloensis, Histiotus magellanicus, and Lasiurus varius).